The Role of Learning Motivation in Students' Academic Achievement - Shobichah, Shobichah (Jurnal Pendidikan Indonesia, 2024)
Education plays a crucial role in developing human resources and improving the quality of life in society. In higher education, academic achievement is often used as an important indicator to evaluate students’ learning outcomes and institutional effectiveness. One of the key psychological factors influencing academic achievement is learning motivation, which drives students to actively engage in learning activities and persist in completing academic tasks. Therefore, this study aims to examine the relationship between learning motivation and students' academic achievement. This study employed a quantitative approach using a correlational research design. The research sample consisted of 120 undergraduate students selected using purposive sampling techniques. Data were collected through a structured questionnaire measuring students’ learning motivation using a five-point Likert scale, while academic achievement was measured using students’ Grade Point Average (GPA). Data analysis was conducted using descriptive statistics, Pearson correlation analysis, and simple linear regression. The results revealed that learning motivation has a positive and statistically significant relationship with students’ academic achievement (r = 0.621, p < 0.01). Regression analysis further indicated that learning motivation significantly predicts academic achievement (β = 0.54, p < 0.001), explaining 38.6% of the variance in students’ academic performance. In conclusion, learning motivation plays a crucial role in enhancing students’ academic achievement. Strengthening students’ motivation through supportive learning environments and effective teaching strategies may contribute to improved academic outcomes in higher education.